Linker-Mediated Recombinational Subcloning of Large DNA Fragments Using Yeast - Raymond, Christopher K.; Sims, Elizabeth H.; Olson, Maynard V. (Genome Research, 2002)
The homologous recombination pathway in yeast is an ideal tool for the sequence-specific assembly of plasmids. Complementary 80-nucleotide oligonucleotides that overlap a vector and a target fragment were found to serve as efficient recombination linkers for fragment subcloning. Using electroporation, single-stranded 80-mers were adequate for routine plasmid construction. A cycloheximide-based counterselection was introduced to increase the specificity of cloning by homologous recombination relative to nonspecific vector background. Reconstruction experiments suggest this counterselection increased cloning specificity by 100-fold. Cycloheximide counterselection was used in conjunction with 80-bp linkers to subclone targeted regions from bacterial artificial chromosomes. This technology may find broad application in the final stages of completing the Human Genome Sequencing Project and in applications of BAC clones to the functional analysis of complex genomes.
10.1101/gr.205201